(untitled) (Bangladesh Journal of Botany, 2024)
To explore the characteristics and the relationship between rapeseed rhizosphere microorganisms, enzyme activities and soil physicochemical properties of rapeseed rhizosphere soil samples was studied. For this purpose the rapeseed rhizosphere soil along with yellow cinnamon soil, paddy soil, yellow brown soil and yellow brown loam soil samples were collected from different soil types in Ankang, Shaanxi. The results indicated that in case of bacteria the Chao1 index of paddy soil was significantly lower than that of the other three soil types, indicating a relatively low abundance of bacterial flora. There was no significant difference in the richness and diversity of fungi in different soil types. At the class level, the relative abundance of bacteria was highest in Alphaproteobacteria, and the relative abundance of fungi was the highest in Sordariomycetes. Heat map analysis showed that there were similarities and differences in the microbial community structure of four different types of soil. Bangladesh J. Bot. 53(3): 783-793, 2024 (September) Special